STRATEGY OF THE MADRASAH PRINCIPAL IN IMPROVING FACILITIES AND INFRASTRUCTURE AT MADRASAH ALIYAH NEGERI 2 PARIGI - Nur Fahriah; Jihan Jihan; Muhammad Nofal; Masmur M; Mastura Muhammad (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
Educational facilities and infrastructure are among the key elements that promote the efficiency of the teaching and learning process in madrasas. This study aims to examine the madrasah principal's strategies for enhancing facilities and infrastructure at MAN 2 Parigi, Mepanga District, Parigi Moutong Regency. This study employs a qualitative methodology with a descriptive research design. Data were gathered through observation, in-depth interviews, and documentation, while data analysis involved data reduction, data display, and drawing conclusions. The findings reveal that the principal's strategy for enhancing facilities and infrastructure involves planning facility requirements based on a priority scale, procuring facilities and infrastructure through government assistance, developing a Madrasah Activity and Budget Plan (RKAM), and conducting ongoing maintenance and supervision. In its execution, the principal involves several stakeholders, including the head of laboratories, the deputy principal for facilities and infrastructure, and administrative staff, to support efficient facility management. The findings also indicate that although certain facilities still require improvement, the overall infrastructure at MAN 2 Parigi is in adequate condition to support learning. Ultimately, the principal's strategy plays a crucial role in supporting facility administration and raising the standard of education in the madrasah.